2016
DOI: 10.1055/s-0042-116315
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal endoscopic submucosal dissection is feasible using the pocket-creation method

Abstract: Duodenal endoscopic submucosal dissection (ESD) requires sophisticated endoscopic techniques because of a high rate of perforation. We introduced the pocket-creation method (PCM) of duodenal ESD to overcome difficulties. The aim of this study was to evaluate the safety and usefulness of ESD using the PCM for superficial tumors of the duodenum. We performed ESD of 17 non-ampullary duodenal lesions using the conventional method and of 28 lesions using the PCM from 2006 to 2015 and retrospectively reviewed the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 19 publications
1
78
2
2
Order By: Relevance
“…A previous report showed that the “pocket creation method (PCM)” is effective for preventing adverse events during duodenal ESD and its intraprocedural perforation rate was 7%, but still higher than that in our trial. Additionally, median times in PCM were 106 min, which were longer compared with our study …”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…A previous report showed that the “pocket creation method (PCM)” is effective for preventing adverse events during duodenal ESD and its intraprocedural perforation rate was 7%, but still higher than that in our trial. Additionally, median times in PCM were 106 min, which were longer compared with our study …”
Section: Discussioncontrasting
confidence: 69%
“…In underwater conditions, superficial lesions float up into the snare as protruding lesions, the duodenal angles become obtuse, and the narrow duodenal lumen is constantly distended . A previous report showed that the “pocket creation method (PCM)” is effective for preventing adverse events during duodenal ESD and its intraprocedural perforation rate was 7%, but still higher than that in our trial. Additionally, median times in PCM were 106 min, which were longer compared with our study …”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Once in the submucosal layer, the subsequent submucosal dissection becomes relatively easy and safe. Miura et al [22] also reported the pocket-creation method, which involves making a pocket in the submucosal layer with a minimal initial mucosal incision after sufficient submucosal injection. In this technique, the tip of the endoscope becomes stable within the pocket, which facilitates the subsequent submucosal dissection.…”
Section: Ingenuities Of Esd In Duodenummentioning
confidence: 99%
“…The technique of endoscopic submucosal dissection (ESD) has recently been developed and accepted as a treatment for duodenal lesions as well as esophageal, gastric, and colorectal lesions [1,2]. However, the duodenum has an anatomically thin muscle wall and is a location in which endoscopic maneuvers and the maintenance of a stable endoscopic view are difficult.…”
Section: Introductionmentioning
confidence: 99%